Ionospheric Disturbances Over the Indian Sector During 8 September 2017 Geomagnetic Storm: Plasma Structuring and Propagation. Issue 3 (16th March 2021) - Alfonsi, L.; Cesaroni, C.; Spogli, L.; Regi, M.; Paul, A.; Ray, S.; Lepidi, S.; Di Mauro, D.; Haralambous, H.; Oikonomou, C.; Shreedevi, P. R.; Sinha, A. K.
Abstract: The series of X and M class flares and associated coronal mass ejections that occurred on the first days of September 2017 induced significant perturbations on the low‐latitude ionospheric electrodynamics. On 8 September in the Indian sector, the storm caused a severe modification of the equatorial electrojet (EEJ) with a consequent variation of the ionospheric structuring and dynamics. In our analysis, we propose an original method to isolate and identify EEJ variations from geomagnetic data and we detect the presence of equatorial plasma bubbles (EPB) from L‐band total electron content (TEC) data in order to understand their movement. Our results provide evidence of independent EPBs appearance freshly generated and inherited from a migrating plasma structure. The EPB (or EPBs) occurring in the south of India is/are freshly generated just above the magnetic equator, and is/are likely triggered by the sudden increase of EEJ just before the local sunset, acting as a pre‐reversal enhancement. The EPB appearing in the North‐East Indian region is associated with a migrating structure, resulting in a northward movement with a velocity of about 650 m/s, possibly testifying the passage of a large‐scale traveling ionospheric disturbance. The occurrence of severe post‐sunset scintillations in the northeastern sector suggests a possible cascade process forming small‐scale irregularities from the migrating EPB. Plain Language Summary: At low latitudes, the ionosphere, the upper part of the atmosphere rich in free electrons, shows a peculiar distribution of its electron density with two maxima around the geomagnetic equator and a minimum above it. When a geomagnetic storm occurs, this configuration can be deeply modified. The way and the persistence of this modification is a matter of study and, to date, still unpredictable. Our study aims to contribute to the advancement of the knowledge in the field presenting a detailed reconstruction of the ionospheric response over India to the geomagnetic storm occurred in early September 2017. We have detected an uneven distribution of free electrons that shows clear evidence of two deep minima (called bubbles): the first one originated elsewhere and then transported over the considered region, the other one freshly and locally produced. Regional analysis of the ionospheric response to the geomagnetic activity can help to improve the space weather forecasting capabilities, supporting the development of alerts and mitigation tools for the users of communication and navigation systems. Key Points: In the post‐sunset hours, the plasma restructuring results into independent equatorial plasma bubbles The migrating structure assumed a wave‐like pattern possibly related to large‐scale traveling ionospheric disturbances moving with a velocity of about 650 m/s The method used to derive prompt penetrating electric fields from the overall ionospheric disturbance is able to discriminate between prompt and delayed disturbance